Distribution and seasonal abundance of Potato Tuber Moth: Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) in Nepal - Giri, Y.P.; Thapa, R.B.; Dangi, N.; Aryal, S.; Shrestha, S.M.; Pradhan, S.B.; Sporleder, M. (Nepal Journals Online, 2014)
Annual monitoring of potato tuber moth (PTM) was made in 2008/09 in15 districts of Nepal to understand the distribution and seasonal abundance. The locally made pheromone trap was installed and observed in 24 hours intervals. The activity of PTM was observed in plain, mid hills (below 2200 masl) and high hill districts. The population of PTM was found more in mid-hills than in plain whereas PTM was absent in high hill districts. The highest average number of PTM was observed in May (480±238 moth/month) with no adult moths in October to December in plain whereas 522±174 moth/month was observed in July and 18±4 moth/month in December in mid-hills of Nepal. The seasonal abundance of PTM observed from March to July (74±63 to 126±100 moth/month) in Plain and March to October (191±157 to 104±60 moth/month) in mid-hills. The understanding of PTM population dynamics could be useful to make suitable management decision. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10794 Int J Appl Sci Biotechnol, Vol. 2(3): 270-274